The Mycobacterium tuberculosis Clp Gene Regulator Is Required for in Vitro Reactivation from Hypoxia-induced Dormancy - McGillivray, Amanda (J Biol Chem, 2015)
Mycobacterium tuberculosis (Mtb) is the leading cause of death from an infectious disease worldwide and is the causative agent of tuberculosis (Chao, M. C., and Rubin, E. J. (2010) Annu. Rev. Microbiol. 64, 293–311). Throughout infection, Mtb encounters a variety of host pressures. Thus, responding to these host stresses via the induction of multiple regulatory networks is needed for survival within the host. The Clp protease gene regulator, Rv2745c (clgR), is induced in response to environmental stress conditions, implicating its potential role in Mtb pathogenesis. Transcriptional activation of genes downstream of Rv2745c occurs in a condition-dependent manner. Our isogenic Mtb:ΔRv2745c mutant expresses a significantly different phenotype upon reaeration conditions. Transcriptional analysis revealed differential gene expression profiles relative to wild-type Mtb. Rv2745c is strongly induced in response to hypoxic and reaeration conditions, implicating a role of Rv2745c in vivo during both establishment of infection and reactivation. We found dysregulation of downstream genes within both the σ(H)/σ(E) regulon as well as the dosR regulon in the isogenic mutant, Mtb:ΔRv2745c. Upon hypoxic and reaeration conditions, Clp protease induction occurred within wild-type Mtb, indicating that activation of clgR, which subsequently leads to Clp protease induction, is crucial for degradation of misfolded proteins and ultimately survival of Mtb upon specific stress conditions. Our data indicate the diverse response of Rv2745c, σ(H) and σ(E) in response to a variety of stress conditions. Activation of Rv2745c in response to various stress conditions leads to differential activation of downstream genes, indicating the diverse role of Rv2745c and its importance for Mtb survival in vivo.